2014
DOI: 10.1017/etds.2013.108
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical properties of spatial discretizations of a generic homeomorphism

Abstract: This paper concerns the link between the dynamical behaviour of a dynamical system and the dynamical behaviour of its numerical simulations. Here, we model numerical truncation as a spatial discretization of the system. Some previous works on well-chosen examples (such as Gambaudo and Tresser [Some difficulties generated by small sinks in the numerical study of dynamical systems: two examples. Phys. Lett. A 94(9) (1983), 412-414]) show that the dynamical behaviours of dynamical systems and of their discretizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Actually, when we perform a lot of simulations, we realize that there are also big variations of the behaviour of the measures (Figure 14): the measure is often well distributed in the torus, and sometimes quite singular with respect to Lebesgue measure (as can be seen in Figure 11). This behaviour is almost identical to that observed in the C 0 case in the neighbourhood of A (see [Gui15c]). neighbourhoods of the boundaries of these charts 'counts for nothing' from the Lebesgue measure viewpoint.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Actually, when we perform a lot of simulations, we realize that there are also big variations of the behaviour of the measures (Figure 14): the measure is often well distributed in the torus, and sometimes quite singular with respect to Lebesgue measure (as can be seen in Figure 11). This behaviour is almost identical to that observed in the C 0 case in the neighbourhood of A (see [Gui15c]). neighbourhoods of the boundaries of these charts 'counts for nothing' from the Lebesgue measure viewpoint.…”
supporting
confidence: 86%
“…We can test whether this property can be observed in simulations or not. T 2 , where g 1 is a small C 1 perturbation of the identity, is way smoother than in the C 0 case (compare Figure 12 with [Gui15c]). Indeed, the measure µ…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Often, physical measure are said to be the ones that can be seen in practice, given they drive the behavior of a positive proportion of the points. However, note that in some cases Guihéneuf [Gui15] has shown that non-physical measures could be actually observed.…”
Section: Physicality and Observabilitymentioning
confidence: 99%
“…Since then, much research has been done in finding "typical" properties of measure-preserving dynamical systems. See, e.g., [28], [26], [1], [27], [2], [5], [3], [12], [4], [33], [21].…”
Section: Introductionmentioning
confidence: 99%